2023
DOI: 10.5530/pj.2022.14.177
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oils Constituent of Etlingera flexuosa (Zingiberaceae), An Endemic Plant from Central Sulawesi

Abstract: Introduction:The essential oils from rhizomes, pseudostems, and leaves of Etlingera flexuosa, an endemic ginger species of Sulawesi, were studied. Methods: The essential oils were extracted using solvent extraction and hydrodistillation methods and analysed by gas chromatography-mass spectrometry (GC-MS). Results: The percentage yield of volatile compounds obtained from solvent extraction method was higher than hydrodistillation. By solvent extraction, sesquiterpenes were found abundantly in rhizomes, pseudost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The rhizomes of the E. flexuosa plant were used in this experiment because it has been utilized empirically in medicine purpose. Besides, the rhizome contains secondary metabolites which are suspected to be immunomodulatory such as flavonoids and alkaloid compounds, both of which have immunomodulatory activity 11,8 and volatile compounds sesquiterpenes 12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rhizomes of the E. flexuosa plant were used in this experiment because it has been utilized empirically in medicine purpose. Besides, the rhizome contains secondary metabolites which are suspected to be immunomodulatory such as flavonoids and alkaloid compounds, both of which have immunomodulatory activity 11,8 and volatile compounds sesquiterpenes 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, E. flexuosa contains the essential oils such as ; monoterpenes, Diterpenes, triterpenes and sesquiterpenes. Pitopang et al 12 reported 76 and 39 essential oil compounds were analyzed using GC-Mass Spectrophotometer by extraction and hydro distillation method respectively. Essential oils (EOs) are a mixture of natural, volatile, and aromatic compounds obtained from plants that can be utilized as immunomodulatory activity 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation